Symposium 7: Identifying Differences in Understandings of PBL, Theory and Interactional Interdependencies - Ryberg, Thomas; Glud, Louise Nørgaard; Buus, Lillian; Georgsen, Marianne (Proceedings of the International Conference on Networked Learning, 2010)
In this paper we discuss networked Problem Based Learning (PBL) and relate this to ideas on web 2.0 learning. Some of the core concepts associated with web 2.0 technologies and practices, such as collaboration, active participation, creation and sharing are well aligned with common interpretations of PBL as a more student-centred pedagogy focusing on students’ active (collaborative) production of knowledge through engaging with problems. While there are some obvious connections between PBL and web 2.0 technologies, many of the thoughts and ideas that have arisen in relation to web 2.0, such as Personal Learning Environments (PLEs), also challenge notions of PBL, but equally hold opportunities to expand our understandings of this pedagogical approach. Likewise, we discuss how certain interpretations of networked learning (Jones & Dirckinck-Holmfeld, 2009; Jones, Ferreday, & Hodgson, 2008) and ideas articulated around the notion of connectivism (Siemens, 2005) might challenge and expand our understandings of PBL. While these discussions are more theoretically oriented our aims in this symposium are to translate these more complex discussions and subtle differences between various theories and pedagogies into more concrete models or concepts that are relevant for practitioners in designing for networked learning. However, the more intimate relations between models and concepts and practical design, will be discussed in Buus et al. (2010).